Maximization of Fundamental Frequency of Composite Stiffened Hypar Shell with Cutout by Taguchi Method - Puja Basu Chaudhuri; Anirban Mitra; Sarmila Sahoo (Mechanics of Advanced Composite Structures)
Composite shells find extensive application in modern civil, aerospace, and marine structures. In order to avoid resonance, such load-carrying shells need to be optimized from a frequency perspective. Composite shell structures often include cutouts for different functional requirements. Obtaining the best combination of design variables like degree of orthotropy, ply orientation, shallowness of the shell, and eccentricity of cutout of laminated shells leads to a problem of combinatorial optimization. This article attempts a numerical study of the free vibration response of composite stiffened hypar shells with cutout using finite element procedure and optimization of different parametric combinations based on the Taguchi approach. Numerical investigations are carried out following the L27 Taguchi design with four design factors, viz., fiber orientation, width/thickness factor of shell, degree of orthotropy, and position of the cutout for different edge constraints. For different shell boundaries considered here, the width/thickness factor emerges as the most influencing factor followed by a degree of orthotropy. The optimum parametric combination for the maximum fundamental frequency of cutout borne stiffened hypar shell is obtained from the analysis.